Characterizing Extra Credit Accumulation by Undergraduate Students - Tushar Ojha; Don R. Hush (IEEE Access)
Most degree-seeking undergraduate students at US universities graduate with a higher number of credit hours than is required for graduation, thereby accumulating extra credits. Although existing literature is rich with studies on extra credit accumulation, most of them are limited to comparing overall credit numbers and thus do not consider the usability of individual credits towards the degree program requirements. This limitation can be attributed to the use of inflexible and/or opaque commercial degree audit tools, which curtails the possible scope of analytics on degree audit data. This work uses a custom-built audit tool that determines an optimal match between individual classes and requirements and then decomposes student credits in the following categories: unusable credits that do not match any degree requirement, excess credits that can satisfy at least one requirement but can be removed without changing overall requirement satisfaction, and applied credits that contribute to requirement satisfaction without excess. Thus, extra credits are decomposed into unusable and excess credits. This paper uses this decomposition to investigate (and quantify) numerous possible reasons for extra credit accumulation including transfer credit loss, program change, financial aid retention, hidden requirements, repeated classes, remedial classes, filler classes, and program requirement characteristics. These investigations compare Transfer and Non-Transfer students, compare extra credit accumulation by college, and explore the term-wise accumulation of extra credits. Surprisingly, this analysis suggests that transfer credit loss (i.e., transfer credits not being accepted or not applying to the chosen major) is not a major contributor to extra credits. It also shows that extra credit accumulation by Transfer and Non-Transfer students is very similar, suggesting that the transfer process may have little influence on extra credit accumulation. Finally, it suggests that extra credit accumulation is likely due to multiple factors without a single dominating factor.